The Second Wuhu Bridge: An Industrialized Application of External Pre-stressed Box-Girder Bridge in China. Issue 2 (1st May 2017) - Hu, Ke; Shi, Xuefei; Ruan, Xin; Liang, Changhai; Liu, Zhiquan
Abstract: The Second Wuhu Bridge is a mega project that will cross the Yangtze River in Anhui Province, China. The main bridge is a cable-stayed bridge with an 806 m main span. Its upcoming connections on both sides are 41.03 km in total. This project needs to be completed within 4 years. To meet this strict time demand, prefabricated, externally prestressed segmental box-girder bridges are utilized using an industrialized method. In this paper, the design and construction of these bridges are introduced. Information about the overall design, cross-sectional design, tendon design, and the precasting and erection techniques are presented. The considerations and optimizations to meet the demands of the industrialized design and construction are explained in detail.